2004
DOI: 10.1248/cpb.52.199
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Protein Secondary Structure by Saccharides of Different Molecular Weights during Freeze-Drying

Abstract: Development of recombinant therapeutic proteins requires rational design of both the formulations and manufacturing processes. [1][2][3][4][5] Freeze-drying is a popular method to retain long-term stability of various proteins that are not sufficiently stable in aqueous solutions, although the stresses incurred during the freeze-drying process often induce partial unfolding and resulting protein aggregation in the rehydrated solutions. [6][7][8] Stable formulation design is required to avoid the biological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
5
19
1
Order By: Relevance
“…Adding polysaccharides such as 0.5% maltose or 0.3% starch enhanced significantly the tolerance of T4 phage to the air-drying effect. This is consistent with previous reports that mentioned the usefulness of different polysaccharides in enhancing the stability of various biologically active compounds against desiccation (7,14,21). This study found that freeze-drying was an efficient method to dry phages with little decrease in phage activity, which would help in developing different paper-coating approaches for the commercial manufacture of phage-containing bioactive membranes.…”
Section: Discussionsupporting
confidence: 94%
“…Adding polysaccharides such as 0.5% maltose or 0.3% starch enhanced significantly the tolerance of T4 phage to the air-drying effect. This is consistent with previous reports that mentioned the usefulness of different polysaccharides in enhancing the stability of various biologically active compounds against desiccation (7,14,21). This study found that freeze-drying was an efficient method to dry phages with little decrease in phage activity, which would help in developing different paper-coating approaches for the commercial manufacture of phage-containing bioactive membranes.…”
Section: Discussionsupporting
confidence: 94%
“…Changes in the distribution of secondary structures of freeze-dried proteins are most commonly assessed by visual comparison of the second derivative of the amide I band (1700-1600 cm -1 ) in the blank corrected FTIR spectra of the sample with a native reference spectrum [10,15,25,26,27,28,29,30]. Freeze-dried formulations were designated as NL if the amide I spectrum was similar (in secondary structural elements distribution) to that of the native LDH before freeze-drying (Fig.…”
Section: Ftir As a Reference Technique To Assign Class Labelsmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FTIR) is widely used to study protein secondary structure in lyophilized solids (2,3). By comparing the FTIR spectrum of the solid protein formulation to the spectrum recorded under comparable solution conditions, an excipient_s ability to protect the protein_s native structure can be evaluated (4)(5)(6)(7). On the basis of such studies, several groups have suggested that the stabilization of the protein by the excipients is the result of protein-excipient interactions (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the FTIR spectrum of the solid protein formulation to the spectrum recorded under comparable solution conditions, an excipient_s ability to protect the protein_s native structure can be evaluated (4)(5)(6)(7). On the basis of such studies, several groups have suggested that the stabilization of the protein by the excipients is the result of protein-excipient interactions (4,6). Izutsu et al (6) reported that higher molecular weight carbohydrates had less protective effect than smaller carbohydrates such as sugars due to a reduction in the number of free hydroxyl groups available to interact with the protein.…”
Section: Introductionmentioning
confidence: 99%